Analisis Yuridis Perampasan Aset Dengan Konsep Non-Conviction Based Asset Forfeiture (NCBAF) Pada Tindak Pidana Korupsi Dan Pencucian Uang - Moch Wahyu; I Made Kariyasa (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
The return of state assets resulting from corruption and money laundering in Indonesia is still relatively low. This is caused by the dependence of the legal system on the concept of Conviction Based Asset Forfeiture (CBAF) which requires a criminal verdict against the perpetrator. Legal problems arise when the perpetrator dies, flees, or is incompetent to stand trial, causing a legal vacuum in asset execution. This study aims to analyze the urgency and mechanism of Non-Conviction Based Asset Forfeiture (NCBAF) as a legal solution. The research method used is normative juridical with statutory, conceptual, and comparative approaches. The results of the study indicate that the application of NCBAF allows asset forfeiture through in rem (civil) lawsuits against the asset itself without waiting for the conviction of the perpetrator. This concept applies the principle of shifting burden of proof and preponderance of evidence. The ratification of the Asset Forfeiture Bill which accommodates NCBAF is a necessity to harmonize national law with UNCAC and increase the effectiveness of state financial recovery.